Diversity of Sordariales Fungi: Identification of Seven New Species of Naviculisporaceae Through Morphological Analyses and Genome Sequencing - Narumon Tangthirasunun; Valérie Gautier; Christophe Lalanne; Lucas Bonometti; Sandrine Cros‐Arteil; Richard D. Hayes; Sarah Calhoun; Robert Riley; Jasmyn Pangilinan; Anna Lipzen; Vivian Ng; Igor V. Grigoriev; et al. (Journal of Fungi, 2025)
and greatly enlarge the genomic data available for the family.
Keywords: Plant Pathogens and Fungal Diseases; Mycorrhizal Fungi and Plant Interactions; Nail Diseases and Treatments